Phytochemical and Biological Investigations of Acokanthera spectabilis - Shanta, Tamanna Ferdous; Rahman, Mohammad S; Kabir, Shaila; Kabir, ANM Hamidul; Begum, Bilkis; Rashid, Mohammad A (Dhaka University Journal of Pharmaceutical Sciences, 2009)
doi: 10.3329/dujps.v7i2.2177 Dhaka Univ. J. Pharm. Sci. 7(2): 187-189, 2008 (December)